Analysis of Factors That Influence Purchasing Decisions on Rajuta Bamboo in Yogyakarta - Marlina Nur Cahyana; Saniatun Nurhasanah; Fitroh Adhilah (www.amertainstitute.com, 2024)
Natural Resource management is an important thing that must be discussed and studied in carrying out national development. One of the natural resources that is easy to find and has many benefits that can be obtained by the people of Indonesia is bamboo. Bamboo crafts are one of the leadinig commodities in Yogyakarta, because the Yogyakarta region is famous as a cultural city that produces many bamboo handicraft is an asset of the Indonesian state. Rattan handicraft exports are an asset of the Indonesia state that is experiencing an increase to reached US301.68 million, this achievement occurred due to the large number of tourists and local people who are interested in bamboo and rattan handicraft. Tourists and local people who are in various kinds of as for the factors that can influence purchasing decisions are store location, social media, electronic word of mouth (e-wom) this method is one ofe the methods of promoting Rajuta Bamboo product. This method is very effective and has a considerable opportunity in marketing activies because if consumers are satisfied with the products the have purchased, they will make purchasing decisions. Data processing was implemented using Partial Least Square (PLS 4.0) and respondents 100 consumer at Rajuta Bamboo in Yogyakarta. This Research state that the three hypoteses are well accepted, namely store location, social media and electronic word of mouth (e-wom) has a positive and significant influenece on purchasing decisions. This research wants to determine the effect of using store location, social media and electronic word of mouth (e-wom) on purchasing decisions on Rajuta Baamboo products in Yogyakarta, both partially and simultaneously.